GlycoBioInformatics - Ranzinger, René (Henry Stewart Talks, 2014)
Carbohydrate structure databases, Glycomics-related databases, Enzyme databases, Databases with glycosylation side information, Glycan binding database, Data analysis software, NMR & Mass spectrometry software, Glycosylation prediction software, 3D structure databases and generation, Data mining, Systems biology